Evaluation of the Common Agricultural Policy's Impact upon Inflation Rate in Central, Eastern and Southern Europe Countries - Ovidiu Stoica; Monica Damian (International Journal of Economics and Financial Issues, 2012)
The goal of this paper is to estimate the inflationary effect of adoption of the Common Agricultural Policy in countries which joined the European Union in 2004, using two approaches. The first one supposes the comparison of consumer food prices before (May-December 2001-2003 and January – April 2002-2004) and after joining the European Union (May – December 2004 and January – April 2005), in all ten states. The second approach consist in the application of a multifactorial regression model for the period 2003-2010 in six countries: the Czech Republic, Hungary, Latvia, Lithuania, Slovakia and Slovenia. The results of the study shows that, contrary to the usual perception, the influence of the agricultural products prices on the food price and, implicitly, on the consumer prices have been relatively low in all the analysed countries, in some countries being counterbalanced by the appreciation of the national currency and the elimination of import custom duties.